Design, development and experiential validation of large stroke welded disk bellows for nuclear industry. (2018) - Krovvidi, S.C.S.P. Kumar; Padmakumar, G.; Raghupathy, S.; Bhaduri, A.K.
This paper presents the design, development of large stroke nested ripple type welded-disc bellows employed in the shield plug of prototype fast breeder reactor. The stroke to length ratio in this case is 0.75. Preliminary design is carried out by equations addressing significant stresses in the bellows, which are derived based on bellows response to various loading. Finite element analysis of the bellows is carried out and fatigue life of the bellows is estimated. Precipitation hardened stainless steel AM350 is selected as material of construction to ensure the bellows are operating in elastic shake down condition. The profile of the bellows and configuration of the welds are arrived by series of mockups. The weld configuration in the welded-disc bellows is not among the accepted configurations given in the codes such as ASME boiler and pressure vessel code, section-III. Hence, the design and manufacturing of the welded disc bellows are validated experimentally with required codal compliance.